Evaluating maintainability metrics in microservices-based student registration systems - Gintoro, Gintoro; Cahyo Nugroho, Eko (Institute of Advanced Engineering and Science, 2025)
As governments redefine educational policy and schools evolve their priorities, more schools must have software that recalibrates with minimal friction. To provide objective guidelines, this study rigorously measures maintainability attributes in a microservices-styled student registration platform, framing the assessment with the ISO/IEC 25010 maintainability specification. We steered each of the standard's maintainability sub-characteristics into defined quantitative constructs, executed in the context of a production microservices topology. Architectural and behavioural views were analysed using Structure101 in static tool runs, and unified modeling language (UML) model inspection anchored the derivation of key metrics, ensuring that stakeholder-defined structures and live microservices concurrency both shaped the evaluation. Results indicate moderate system modularity with average component dependency (ACD) of 2.14, propagation cost (PC) of 10.2%, and identification of one non-trivial cycle group involving three classes. Cohesion analysis revealed structural improvement opportunities in core classes such as admin and candidate lack of cohesion in methods 4 (LCOM4)≥2). The inheritance structure shows optimal characteristics with shallow depth (depth of inheritance tree (DIT)≤1), and controlled breadth (number of children (NOC)=2), supporting both analyzability and modifiability. These findings provide actionable insights for enhancing system maintainability in microservices architectures, particularly for educational domain applications requiring frequent policy adaptations.